A colorless and transparent polyimide composite film with high water vapor barrier and preparation method thereof
By wrapping and oriented glass microsheets in the polyimide-based film, a high-water-gas-barrier colorless transparent polyimide composite film is formed, which solves the problem of insufficient hardness and barrier properties of the CPI film, and achieves high light transmission and high light transmission Hardness and good bending resistance, suitable for flexible OLED displays.
Patent Information
- Application Number
- CN202010886960.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-08-28
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2040-08-28
AI Technical Summary
In the application of flexible OLED displays, the surface hardness and water-gas barrier properties do not meet the actual requirements, and the CPI-glass composite film is not flexible and flexible enough, so it is difficult for the prior art to directly melt the glass at high temperatures.
The polyimide-based film formed by curing polyamic acid precursor or polyimide solution is used to wrap optical or non-optical glass microsheets. The glass microsheets are oriented consistently through rolling and bidirectional stretching technology to form a high Water-gas-blocking colorless transparent polyimide composite film.
The light transmittance, hardness and bending resistance of the polyimide composite film are significantly improved, and the problems of insufficient hardness and barrier properties of the CPI film are overcome, while maintaining good flexibility and bendingability.
Smart Images

Figure CN111892817B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyimide films, and in particular to a colorless and transparent polyimide composite film with high water vapor barrier properties and a preparation method thereof. Background Art
[0002] In the application of flexible OLED display, the transparency and flexibility of CPI film basically meet the requirements of practical application, but the surface hardness and water vapor barrier performance of CPI film do not meet the requirements of practical application. At present, some technicians apply organic hardening layer or inorganic glass material on CPI film to obtain high light transmittance, high water resistance and high hardness performance, but this method greatly affects the flexibility of CPI-glass composite film, making the foldability and bendability of CPI-glass composite film far from meeting the requirements of practical use. In addition, during the preparation process, due to the large difference in thermal expansion coefficients between CPI film and glass, and the preparation temperature difference of at least 300°C, CPI-glass composite film will produce delamination under thermal stress, so it is impossible to directly melt-coat glass on CPI film. Based on the above problems, CPI-glass composite film and its preparation technology still need to be improved. Summary of the invention
[0003] The present invention aims at the defects in the prior art such as insufficient barrier property and hardness of CPI film and the bendability of CPI-glass composite film failing to meet the actual use requirements, and provides a new high water vapor barrier colorless transparent polyimide composite film and a preparation method thereof.
[0004] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:
[0005] A high water vapor barrier colorless transparent polyimide composite film comprises a polyimide base film and a glass micro-sheet. The polyimide base film is formed by curing a polyamic acid precursor or a polyimide solution, and further comprises an organic filler, which is dispersed in the polyimide base film. The polyimide base film wraps the glass micro-sheet. The angle between the glass micro-sheet and the plane of the polyimide base film is α, 0°≤α≤30°. The thickness of the polyimide base film is 15μm-200μm, the thickness of the glass micro-sheet is 50nm-5μm, the diameter of the glass micro-sheet is 1μm-150μm, and the volume ratio of the polyimide base film to the glass micro-sheet is 1:0.05-0.25:1.
[0006] The present invention adopts a polyimide-based film formed by curing a polyamic acid precursor or a polyimide solution, which has the advantage of uniform distribution, and the surface layer is denser and more uniform, thereby reducing the surface defect rate of the polyimide-based film. The glass microchips used in the present invention can be selected from optical or non-optical glass microchips. As a preferred embodiment, glass microchips produced by Glassflake Ltd. can be used, and the glass microchips are chemically corroded to obtain glass microchips that meet the size requirements. In the film layer structure of the polyimide-based film wrapped glass microchips, since the glass microchips have excellent light transmittance, the light transmittance of the polyimide composite film can be significantly improved. At the same time, the introduction of the glass microchips can enhance the surface hardness of the polyimide composite film, overcoming the defect of insufficient hardness of the existing CPI film.
[0007] The glass microsheets are wrapped in the polyimide base film, which can significantly reduce the area of water vapor penetration and play an excellent water vapor barrier role, thereby overcoming the defect of insufficient barrier properties of CPI film; in addition, when the polyimide composite film is bent, the glass microsheets are wrapped in the polyimide base film and will not bend significantly, thereby allowing the polyimide composite film to maintain good bending resistance, overcoming the defect of insufficient bending properties of existing CPI-glass composite films.
[0008] Preferably, in the above-mentioned colorless and transparent polyimide composite film with high water vapor barrier, the edges of the glass microsheets have cross-linkable groups.
[0009] The cross-linkable groups can enhance the lateral dispersion of the glass microsheets, thereby further enhancing the water vapor barrier effect of the glass microsheets, and at the same time enable the polyimide composite film to maintain good bending resistance.
[0010] Preferably, in the above-mentioned colorless and transparent polyimide composite film with high water vapor barrier, the glass microsheets are interconnected through the cross-linkable groups.
[0011] Through the above structure, the lateral connection and dispersion of the glass microsheets can be further enhanced, thereby further enhancing the water vapor barrier effect of the glass microsheets, while enabling the polyimide composite film to maintain good bending resistance.
[0012] Preferably, in the above-mentioned colorless and transparent polyimide composite film with high water vapor barrier, the organic filler is a dispersant, and the weight ratio of the glass microsheets to the dispersant is 1:0.01 to 1:0.05.
[0013] Adding the dispersant in the above weight ratio can enhance the dispersion of the glass microflakes in the polyimide-based film.
[0014] Preferably, the method for preparing the above-mentioned colorless and transparent polyimide composite film with high water vapor barrier comprises the following preparation steps:
[0015] S1: Take a polyamic acid precursor or a polyimide solution, add glass microsheets and an organic filler, place in a stirrer for mixing, and stir at 20 to 50° C. for 60 min to 16 h to obtain a composite slurry;
[0016] S2: taking a rigid substrate, coating the composite slurry on the rigid substrate, light curing at room temperature for 30 seconds to 5 minutes or thermal curing at 60 to 200° C. for 0.5 to 2 hours, so that the polyamic acid precursor or polyimide solution in the composite slurry is converted into a semi-cured polyimide-based film, thereby obtaining a semi-cured polyimide composite film;
[0017] S3: placing the semi-cured polyimide composite film in a rolling and stretching device, rolling it at 60-100° C., and then biaxially stretching it at 150-300° C. to obtain the polyimide composite film with consistent orientation of glass microsheets;
[0018] S4: The polyimide composite film obtained in step S3 is photocured for 30 seconds to 5 minutes or thermally cured in an environment of 200 to 350° C. for 0.5 hours to 5 hours to completely cure it, thereby finally obtaining a colorless and transparent polyimide composite film with high water vapor barrier.
[0019] In step S1 of the present invention, adding an organic filler and stirring sufficiently can ensure that a uniform composite slurry is obtained, avoid the glass microsheets from agglomerating in large quantities, and ensure that subsequent reactions proceed smoothly.
[0020] In step S2 of the present invention, the semi-cured polyimide composite film obtained has the advantage of good fluidity, which can ensure that the glass micro-sheets have good fluidity in the polyimide composite film, and is conducive to obtaining glass micro-sheets with consistent orientation.
[0021] In step S3 of the present invention, the semi-cured polyimide composite film is first rolled, and then biaxially stretched, so that the glass micro-sheets wrapped therein have a uniform and consistent orientation.
[0022] In step S4 of the present invention, the use of a thermal curing or photocuring process is beneficial for obtaining a high water vapor barrier colorless and transparent polyimide composite film with excellent optical, mechanical and thermal properties.
[0023] Preferably, in the above-mentioned method for preparing a colorless and transparent polyimide composite film with high water vapor barrier, in the step S3, the thickness of the semi-cured polyimide composite film is reduced by 2 to 15% when rolling is completed.
[0024] The invention adopts a rolling process to prepare a uniform and dense polyimide composite film, and is conducive to obtaining glass micro-sheets with optimal parallel orientation.
[0025] Preferably, in the above-mentioned method for preparing a colorless and transparent polyimide composite film with high water vapor barrier, in step S3, the stretching amplitude during biaxial stretching is 1 to 10%.
[0026] The invention adopts a biaxial stretching range of 1-10%, which can avoid the glass micro-sheet from breaking and is conducive to obtaining the glass micro-sheet with the best parallel orientation, while ensuring that the polyimide composite film obtains the best mechanical properties.
[0027] Compared with the prior art, the present invention has the following outstanding beneficial effects:
[0028] The high water vapor barrier colorless transparent polyimide composite film finally prepared by the present invention has excellent bendable and foldable mechanical properties, high water vapor barrier properties, and high hardness, which are properties that a single polyimide film or ultra-thin glass cannot have at the same time; BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a structural schematic diagram of the present invention;
[0030] Figure 2 It is a schematic diagram of the structure of the present invention when bent 180°. DETAILED DESCRIPTION
[0031] The following is combined with Figure 1-2 The present invention is further described in detail with specific embodiments, but they are not intended to limit the present invention:
[0032] Example 1
[0033] A high water vapor barrier colorless transparent polyimide composite film comprises a polyimide base film 1 and a glass microchip 2. The polyimide base film 1 is formed by curing a polyamic acid precursor or a polyimide solution, and further comprises an organic filler, which is dispersed in the polyimide base film 1. The polyimide base film 1 wraps the glass microchip 2. The angle between the glass microchip 2 and the plane of the polyimide base film 1 is α, 0°≤α≤30°, the thickness of the polyimide base film 1 is 15μm, the thickness of the glass microchip 2 is 50nm, the diameter of the glass microchip 2 is 1μm, and the volume ratio of the polyimide base film 1 to the glass microchip 2 is 1:0.05.
[0034] Preferably, the edges of the glass microsheets 2 have cross-linkable groups.
[0035] Preferably, the glass microsheets 2 are connected to each other via the cross-linkable groups.
[0036] Preferably, the organic filler is a dispersant, and the weight ratio of the glass microflakes 2 to the dispersant is 1:0.01.
[0037] Preferably, the method comprises the following preparation steps:
[0038] S1: Take a polyamic acid precursor or a polyimide solution, add glass microsheets 2 and an organic filler, place in a stirrer for mixing, and stir at 20° C. for 60 minutes to obtain a composite slurry;
[0039] S2: taking a rigid substrate, coating the composite slurry on the rigid substrate, light curing at room temperature for 30 seconds or thermal curing at 60° C. for 0.5 hours, so that the polyamic acid precursor or polyimide solution in the composite slurry is converted into a semi-cured polyimide base film 1, thereby obtaining a semi-cured polyimide composite film;
[0040] S3: placing the semi-cured polyimide composite film in a rolling and stretching device, rolling it at 60° C., and then biaxially stretching it at 150° C. to obtain the polyimide composite film with the glass microsheets 2 having a consistent orientation;
[0041] S4: The polyimide composite film obtained in step S3 is photocured for 30 seconds or thermally cured for 0.5 hours in an environment of 200° C. to completely cure it, thereby finally obtaining a colorless and transparent polyimide composite film with high water vapor barrier.
[0042] Preferably, in step S3, the thickness of the semi-cured polyimide composite film is reduced by 2% when rolling is completed.
[0043] Preferably, in step S3, the stretching amplitude during biaxial stretching is 10%.
[0044] Example 2
[0045] A high water vapor barrier colorless and transparent polyimide composite film comprises a polyimide base film 1 and a glass micro-chip 2. The polyimide base film 1 is formed by curing a polyamic acid precursor or a polyimide solution, and further comprises an organic filler, which is dispersed in the polyimide base film 1. The polyimide base film 1 wraps the glass micro-chip 2. The angle between the glass micro-chip 2 and the plane of the polyimide base film 1 is α, 0°≤α≤30°. The thickness of the polyimide base film 1 is 200 μm, the thickness of the glass micro-chip 2 is 5 μm, the diameter of the glass micro-chip 2 is 150 μm, and the volume ratio of the polyimide base film 1 to the glass micro-chip 2 is 0.25:1.
[0046] Preferably, the edges of the glass microsheets 2 have cross-linkable groups.
[0047] Preferably, the glass microsheets 2 are connected to each other via the cross-linkable groups.
[0048] Preferably, the organic filler is a dispersant, and the weight ratio of the glass microflakes 2 to the dispersant is 1:0.05.
[0049] Preferably, the method comprises the following preparation steps:
[0050] S1: Take a polyamic acid precursor or a polyimide solution, add a glass microsheet 2 and an organic filler, place in a stirrer for mixing, and stir at 50° C. for 16 hours to obtain a composite slurry;
[0051] S2: taking a rigid substrate, coating the composite slurry on the rigid substrate, light curing at room temperature for 5 minutes or thermal curing at 200° C. for 2 hours, so that the polyamic acid precursor or polyimide solution in the composite slurry is converted into a semi-cured polyimide base film 1, thereby obtaining a semi-cured polyimide composite film;
[0052] S3: placing the semi-cured polyimide composite film in a rolling and stretching device, rolling it at 100° C., and then biaxially stretching it at 300° C. to obtain the polyimide composite film with consistent orientation of the glass microsheets 2;
[0053] S4: The polyimide composite film obtained in step S3 is photocured for 5 minutes or thermally cured in an environment of 350° C. for 5 hours to completely cure it, thereby finally obtaining a colorless and transparent polyimide composite film with high water vapor barrier.
[0054] Preferably, in step S3, the thickness of the semi-cured polyimide composite film is reduced by 15% when rolling is completed.
[0055] Preferably, in step S3, the stretching amplitude during biaxial stretching is 1%.
[0056] Example 3
[0057] A high water vapor barrier colorless and transparent polyimide composite film comprises a polyimide base film 1 and a glass microchip 2. The polyimide base film 1 is formed by curing a polyamic acid precursor or a polyimide solution, and further comprises an organic filler, which is dispersed in the polyimide base film 1. The polyimide base film 1 wraps the glass microchip 2. The angle between the glass microchip 2 and the plane of the polyimide base film 1 is α, 0°≤α≤30°. The thickness of the polyimide base film 1 is 100 μm, the thickness of the glass microchip 2 is 2.5 μm, the diameter of the glass microchip 2 is 70 μm, and the volume ratio of the polyimide base film 1 to the glass microchip 2 is 0.62:0.52.
[0058] Preferably, the edges of the glass microsheets 2 have cross-linkable groups.
[0059] Preferably, the glass microsheets 2 are connected to each other via the cross-linkable groups.
[0060] Preferably, the organic filler is a dispersant, and the weight ratio of the glass microflakes 2 to the dispersant is 1:0.03.
[0061] Preferably, the method comprises the following preparation steps:
[0062] S1: Take a polyamic acid precursor or a polyimide solution, add a glass microsheet 2 and an organic filler, place in a stirrer for mixing, and stir at 35° C. for 8 hours to obtain a composite slurry;
[0063] S2: taking a rigid substrate, coating the composite slurry on the rigid substrate, light curing at room temperature for 3 minutes or thermal curing at 130° C. for 1 hour, so that the polyamic acid precursor or polyimide solution in the composite slurry is converted into a semi-cured polyimide base film 1, thereby obtaining a semi-cured polyimide composite film;
[0064] S3: placing the semi-cured polyimide composite film in a rolling and stretching device, rolling it at 80° C., and then biaxially stretching it at 260° C. to obtain the polyimide composite film with the glass microsheets 2 having a consistent orientation;
[0065] S4: The polyimide composite film obtained in step S3 is photocured for 3 minutes or thermally cured in an environment of 280° C. for 3 hours to completely cure it, thereby finally obtaining a colorless and transparent polyimide composite film with high water vapor barrier.
[0066] Preferably, in step S3, the thickness of the semi-cured polyimide composite film is reduced by 8% when rolling is completed.
[0067] Preferably, in step S3, the stretching amplitude during biaxial stretching is 5%.
[0068] Example 4
[0069] The polyimide composite films obtained in the above embodiments and the existing PI film produced by KOLON Industries, Ltd. were taken as comparative examples to test the four properties of pencil hardness, bending resistance, light transmittance, and water vapor barrier rate. The test method is as follows:
[0070] 1. Pencil hardness test: Use a pencil hardness tester to test the pencil hardness according to the method of GB / T 6739 "Paint and varnish pencil method for determination of paint film hardness";
[0071] 2. Bending resistance test: Use a hinged bending test machine, set the bending radius to 3mm, the bending angle to 0-180°, and the bending speed to 20rpm / min, and conduct a reciprocating bending test;
[0072] 3. Light transmittance test: Tested using ASTM D1003 standard;
[0073] 4. Water vapor barrier rate test: The test is conducted using ASTM International-ASTM D7709-11 standard.
[0074] The performance parameters of the polyimide composite films obtained in various embodiments of the present invention and the comparative examples are shown in Table 1:
[0075] Table 1
[0076] sample Pencil hardness Bending resistance Light transmittance Water vapor barrier rate Example 1 3H ≥200,000 times 90.8% <![CDATA[5.8x10 -2 g / m 2 ·day]]> Example 2 4H ≥200,000 times 89.8% <![CDATA[3.2x10 -5 g / m 2 ·day]]> Example 3 3H ≥200,000 times 90.2% <![CDATA[8.2x10 -5 g / m 2 ·day]]> Comparative Example 1 2H ≥200,000 times 89.2% <![CDATA[1.1g / m 2 ·day]]>
[0077] In conclusion, the above is only a preferred embodiment of the present invention, and all equivalent changes and modifications made within the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A colorless and transparent polyimide composite film with high water vapor barrier, comprising a polyimide base film (1) and a glass microsheet (2), wherein the polyimide base film (1) is formed by curing a polyamic acid precursor or a polyimide solution, and characterized in that: The edges of the glass microflakes (2) have cross-linkable groups, and the glass microflakes (2) are connected to each other via the cross-linkable groups; The polyimide composite film further comprises an organic filler, which is a dispersant. The organic filler is dispersed in the polyimide-based film (1). The polyimide-based film (1) wraps the glass microchip (2). The angle between the glass microchip (2) and the plane of the polyimide-based film (1) is α, 0°≤α≤30°. The thickness of the polyimide-based film (1) is 15 μm to 200 μm, the thickness of the glass microchip (2) is 50 nm to 5 μm, the diameter of the glass microchip (2) is 1 μm to 150 μm, and the volume ratio of the polyimide-based film (1) to the glass microchip (2) is 1:0.05 to 0.25:
1.
2. The colorless and transparent polyimide composite film with high water vapor barrier according to claim 1, characterized in that: The weight ratio of the glass microsheets (2) to the dispersant is 1:0.01 to 1:0.
05.
3. The method for preparing a colorless and transparent polyimide composite film with high water vapor barrier according to claim 1, characterized in that: The method comprises the following preparation steps: S1: taking a polyamic acid precursor or a polyimide solution, adding a glass microsheet (2) and an organic filler, placing the mixture in a stirrer for mixing, and stirring at 20 to 50° C. for 60 minutes to 16 hours to obtain a composite slurry; S2: taking a rigid substrate, coating the composite slurry on the rigid substrate, and thermally curing the composite slurry at 60 to 200° C. for 0.5 to 2 h to convert the polyamic acid precursor or polyimide solution in the composite slurry into a semi-cured polyimide-based film (1), thereby obtaining a semi-cured polyimide composite film; S3: placing the semi-cured polyimide composite film in a rolling and stretching device, rolling it at 60-100° C., and then biaxially stretching it at 150-300° C. to obtain the polyimide composite film with the glass microsheets (2) in a uniform orientation; S4: The polyimide composite film obtained in step S3 is thermally cured in an environment of 200 to 350° C. for 0.5 to 5 hours to completely cure it, thereby finally obtaining a colorless and transparent polyimide composite film with high water vapor barrier.
4. The method for preparing a colorless and transparent polyimide composite film with high water vapor barrier according to claim 3, characterized in that: In the step S3, the thickness of the semi-cured polyimide composite film is reduced by 2 to 15% when rolling is completed.
5. The method for preparing a colorless and transparent polyimide composite film with high water vapor barrier according to claim 3, characterized in that: In the step S3, the stretching amplitude during biaxial stretching is 1 to 10%.
